Analysis of 5G Capacity in Line-Of-Sight Condition of Urban Macro (UMa) Using 3.5 GHz Frequency - Yaser, Muhammad (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study is projected to be the initial design for the implementation of 5G technology, particularly in the Urban Macro (UMa) scenario, with a frequency of 3.5GHz and a bandwidth of 100 MHz. 3GPP (3rd Generation Partnership Project) TR 38.901 recommends performing performance analysis with line-of-sight (LOS) situations using the propagation model urban macro (uMa). In this study, 100 users are distributed at random distances to examine system capacity using the frequency reuse factors K = 1/3 and K = 1/7. According to the calculation results, this study demonstrates that system capacity is dependent on user distribution arrangement and the frequency reuse factor approach used. A high frequency reuse factor increases bandwidth efficiency and yields more optimum capacity. Furthermore, distributing users near the base station will boost capacity.